1991
DOI: 10.1007/bf02441662
|View full text |Cite
|
Sign up to set email alerts
|

Method to evaluate the skill level in fast locomotion through myoelectric and kinetic signal analysis

Abstract: The paper describes a method aimed at providing objective diagnostic testing of skilled locomotor stereotypes. Bioelectric muscle activity indices and ground reaction force data are used to represent a movement structure, in a schematized way, using discrete states in time. Athletes were asked to perform one specific movement structure: a backward somersault from the standing position. Mathematical analyses of measured signals reveal the significance, for the skill level evaluation, of parameters reflecting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The flight time varied significantly ( p < 0.05): it was longer during the SB s270 than during the SB s90 and the SB s180 . The flight times in SB s270 and SB s90 were comparable to the data published by Mkaouer et al (2012), Medved et al (1995) and Medved and Tonkovíc (1991). Also, the vertical elevation of the COM varied considerably in the flight phase ( p < 0.05).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The flight time varied significantly ( p < 0.05): it was longer during the SB s270 than during the SB s90 and the SB s180 . The flight times in SB s270 and SB s90 were comparable to the data published by Mkaouer et al (2012), Medved et al (1995) and Medved and Tonkovíc (1991). Also, the vertical elevation of the COM varied considerably in the flight phase ( p < 0.05).…”
Section: Discussionsupporting
confidence: 88%
“…The greatest indices of vertical force (Fy) were attained during the SB s90 followed by SB s270 and SB s180 . Medved et al (1995), Medved and Tonkovic (1991) and Lacouture et al (1989) have reported similar values of the horizontal force developed during the SB s270 and vertical force during the SB s90 , respectively.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Empirical research evidence shows us that the value of this index, estimated by calculating correlation coefficients of smoothed EMG signals of pairwise measured m.gastrocnemi-i, amounts to approximately 0.8, being a threshold of the high skill level. 9 The area of gait pathology diagnostics offers its own criteria, as a result of accumulated experimental evidence. 15 The essence of the system's function is in comparing the simulated and measured signals.…”
Section: Locomotion Simulation Facility and Data Comparisonmentioning
confidence: 99%
“…It bears upon the previously reported concept of signal synthesis, 8 and a recently developed system of EMG and kinetic signal-based locomotion diagnostics. 9 The enhanced system's concept has been preliminarily reported in reference 10.…”
Section: Introductionmentioning
confidence: 99%